Oral health and quality of life of pregnant women: the influence of sociodemographic factors - Santos Pacheco, Karina Tonini dos; Sakugawa, Keiko Oliveira; Martinelli, Katrini Guidolini; Degli Esposti, Carolina Dutra; Pacheco Filho, Antonio Carlos [UNESP]; Saliba Garbin, Clea Adas [UNESP]; Isper Garbin, Artenio Jose [UNESP]; Santos Neto, Edson Theodoro (Abrasco-assoc Brasileira Pos-graduacao & Saude Coletiva, 2020)
This study aimed to evaluate the relationship between sociodemographic factors and the impact on Oral Health-Related Quality of Life (OHR-QoL) in Brazilian pregnant women users of the Unified Health System. This is a cross-sectional epidemiological study developed with pregnant women living in two regions with different sociodemographic characteristics. In total, 1,777 puerperae were interviewed. A structured and previously tested questionnaire collected sociodemographic variables, and the Oral Health Index Profile (OHIP-14) assessed the impact on the OHR-QoL. The statistical analysis was performed using the Chi-square test and multiple logistic regression, both with a significance of 5%. The psychological discomfort realm was the only one with a difference between the puerperae of the RMGV and the MRSM (p=0.042). The following variables were associated with the impact on the OHR-QoL: residing in the RMGV (OR=1.69; 95%CI: 1.16-2.47); having a low level of schooling (OR=1.80; 95%CI: 1.03-3.18) and visit to the dentist during pregnancy (OR=2.15, 95%CI: 1.50-3.07). Sociodemographic factors should be considered in the planning of oral health actions of pregnant women, as they influence the impact on the OHR-QoL.
Keywords: Maternal and Child Health; Quality of life; Oral Health; Demographic Data